Temporomandibular disorders according to the stress level between dentistry students in an Ecuadorian university - Padilla-Correa, Fernanda (2025)
Temporomandibular joint (TMJ) disorders affect both the bone, muscles and nervous components, with multifactorial etiology and a complex and interdisciplinary treatment. Our aim was to analyze the relationship between the temporomandibular disorders (TMD) and stress levels of preprofessional dentistry internships students. Internships are carried out during the last two years of the degree, and generate important stress levels, by the rule of completing a serial of dental procedures to get promoted to the next level in their career. Sometimes students must pay for those treatments only to meet these requirements. We applied two questionnaires to students of the last four semesters of dentistry at an Ecuadorian university. Scales applied were the Fonseca Amnestic Index for TMD, and the Global Stress Perception Scale. We found that the prevalence of TMD was 99,08%; with mild level in 15,61%. The moderate level was 63,90%; and severe level in 3,90%. In the other side, the moderate level of stress was in 91,71% of participants; 3,90% had mild stress level and 4,39% severe. The Chi-square was 0,001 between both variables, which indicates a relationship between the stress level and TMD of dentistry students.